Understanding the sub-lethal effects of ZNO nanoparticles and its implications to skin repair - Wu, Zhuoran (2018)
Understanding the cellular responses to nano zinc oxide particles (Nano-ZnO) (<100 nm) is key to its successful novel exploitation in nanomedicine and bio-nanotechnology. Unlike other conventional inorganic compounds, zinc is an essential co-factor for numerous enzymes that are known to regulate a wide spectrum of fundamental cellular activities such as redox homeostasis, metabolism and signal transductions. In human, as many as 3000 proteins have been revealed to contain Zn2+. In this regard, Nano-ZnO can be considered as a unique class of biologically active nanomaterials that can either disrupt (at toxic concentration) or support (at non-toxic concentration) cellular functions. While studies have shown that high concentrations of Nano-ZnO can trigger oxidative stress-mediated cell death via the generation of reactive oxygen species (ROS), little is known about the effects of Nano-ZnO and its role in mediating ROS signalling in the low-dose range. Inspired by recent demonstrations of biological systems capable of reciprocating to low level of oxidative stress via the process of cell adaptation, this project seeks to examine whether (i) cells can adapt to low dose of Nano-ZnO, (ii) understand the underlying mechanism underpinning the adaption process and (iii) conduct proof-of-concept studies to unveil the biological consequences of Nano-ZnO mediated adaption.